Acts of Rebellion: The Subversion of Traditional Gender Roles and the Politics of Desire in Roy’s ‘The God of Small Things’ - Maqbool, Rimsha; Munir, Haniya (Annals of Human and Social Sciences, 2025)
This article investigates the ways in which Arundhati Roy’s The God of Small Things challenges and subverts traditional gender roles through subtle yet powerful acts of personal resistance. Set against the backdrop of a rigidly stratified South Indian society, the novel foregrounds characters—most notably Ammu, Rahel, and Velutha—whose lives and desires conflict with the dominant social order shaped by patriarchy, caste hierarchy, and cultural orthodoxy. Through Judith Butler’s Theory of Gender Performativity (1990) , the paper examines how personal desire becomes a form of political defiance. Ammu’stransgressive love, Rahel’s resistance to conventional femininity, and Velutha’s socially forbidden relationship with an upper-caste woman all reflect an intimate rebellion against structures that seek to discipline gender, sexuality, and identity. Roy’s narrative style—nonlinear, fragmented, and emotionally rich—further mirrors the thematic disruption of normative constructs. The research shows that ‘The God of Small Things’ doesn’t just tell a story about love, loss, and rebellion—it also critiques the rigid gender roles that dominate both family and society. Through the novel’s fractured narrative and multi-layered storytelling, Roy makes it clear that the tension between personal desires and societal pressures is not only heartbreaking but dangerous. By subverting traditional gender binaries and showing the consequences of breaking these rules, Roy reveals the deep scars that these societal constraints leave behind. The findings here open up many exciting possibilities for future research, especially in exploring how other postcolonial works handle gender and sexuality. Future studies could look at how queer identities challenge the national and social boundaries often seen in postcolonial literature. Roy’s portrayal of non-normative desires and rebellion invites ongoing conversations about gender fluidity and feminist movements, particularly in the Global South.